Will a global subsidy of artemisinin-based combination treatment (act) for malaria delay the emergence of resistance and save lives? - Laxminarayan, Ramanan (Policy research working paper, 2005)
"Artemisinin-based combination treatments (ACTs) are seen as an important tool in the global effort to roll back malaria. With rapidly increasing parasite resistance to chloroquine in many parts of the world, there is greater international recognition of the need for both a different antimalarial and a coordinated malaria treatment strategy to ensure that resistance does not needlessly cut short the useful therapeutic life of any successor drug to chloroquine. The effectiveness of antimalarial drugs is a global public good, of particular value in malarious regions that also are among the most economically impoverished parts of the world. Inappropriate drug use in neighboring countries reduces the incentive of any given country to deploy drug regimens that may be rapidly undermined by resistance originating outside their borders. Therefore, a case can be made for globally coordinated action to protect the effectiveness of these valuable drugs. Translating this case to one for a global subsidy is not straightforward. On the one hand, in the absence of such a subsidy to ensure that ACTs are comparably priced to monotherapies, increasing monotherapy of artemisinin and other antimalarials that would be used along with artemisinin in ACT will hasten the demise of this drug. On the other hand, a global subsidy would greatly increase the use and potential misuse of ACTs and could result in resistance emerging at a more rapid rate. This study finds that a subsidy to ACTs is likely to slow the rate of emergence of resistance to artemisinin and partner drugs, even if such a subsidy were to increase the use of ACTs significantly. This conclusion is robust to alternative assumptions regarding the responsiveness of demand to the lower price for ACTs and a wide range of epidemiological and economic parameters.